(untitled) (Medina-Te : Jurnal Studi Islam, 2022)
This paper examines the Tafsir al-Maraghi by Shaykh Ahmad Mustafa al-Maraghi. The results of this study conclude that the methodology of Tafsir al-Marâghi has its own characteristics, in terms of systematic writing, al-Maraghi writes down the verses of the Qur'an first at the beginning of the discussion; next he explains each vocabulary; explain the meaning of the verse globally; explain the reasons for the revelation of the verse, setting aside terms that are difficult to understand; avoiding irrational stories; selective in including the isrā'iliyat story; and adapt to the situation, conditions and muhkatab. As for the method used in al-Maraghi's interpretation, namely using the ijmali and tahlili methods, while the style used is adabi Ijtima'i which is oriented to life literature. This study uses library research by using literatures related to the Al-Maraghi Tafsir Methodology. There are two sources of data in this study, namely primary data and secondary data. This type of research is descriptive-inductive, which tries to explain clearly and systematically about the Al-Maraghi Tafsir Methodology taken and compiled from several authoritative sources. After the data has been collected, it is then reduced and described again, so that it is more clear and systematic, so that it can answer the research being studied